Frequency‐Dependent Moment Tensors of Induced Microearthquakes. Issue 12 (20th June 2019) - Yu, Changpeng; Vavryčuk, Václav; Adamová, Petra; Bohnhoff, Marco
Abstract: Analysis of 984 induced microearthquakes from The Geysers geothermal reservoir in California reveals that the retrieved moment tensors depend on the frequency band of the inverted waveforms. The observed dependence is more significant for the percentages of the double‐couple, compensated linear vector dipole, and isotropic (ISO) components than for the focal mechanisms. The average root‐mean‐square of the moment tensors obtained in different frequency bands is correlated with spectra of ambient noise. The percentages of double‐couple and ISO components tend to decrease and increase with the upper cutoff frequency ( f u ), respectively. This suggests that shear rupture radiates energy preferentially in a lower frequency band and tensile rupture in a higher frequency band. Events displaying a strong increase of the ISO with f u are confined within the same depth interval as the injection points. This might be related to the strong thermoelastic effects in the vicinity of injection points that promote opening of small cracks adjacent to the main fractures. Plain Language Summary: Moment tensor (MT) describes shear and tensile motions in the earthquake source. The components of MT are usually assumed to be independent of the frequency. However, this assumption may not satisfy the complex rupture process of induced microearthquakes. We use a novel approach to investigate 984 induced microearthquakes from The Geysers geothermal reservoir in California and find that the retrieved MTs depend on the frequency band of input waveforms. The observed dependence is more significant for the components of MT measuring the proportions of seismic energy than for the components determining fault geometry. The component of MT describing shear motion shows a different frequency dependence than that describing tensile motion, suggesting that these two motions occur on the structures with different spatial scales. A subset of seismic events is identified to have a distinct feature of frequency dependence. These events only occur in the layer where the cool water is injected into the hot reservoir and do not migrate downward as the other events. This might be related to the strong thermal effects in the vicinity of injection points that promote the opening of small cracks adjacent to the main fractures. Key Points: Moment tensor components of induced earthquakes from The Geysers geothermal reservoir in California show significant frequency dependence DC and ISO components tend to decrease and increase with frequency, respectively, implying different properties of shear and tensile ruptures Events with a significant increase of ISO component with frequency are confined within the same depth interval as the injection points